Application of Knowledge Discovery and Data Mining Using Artificial Intelligence: A Performance Analysis - Mohammad Asim Khan, Sharik Ahmad (International Journal of Advanced Science and Technology, 2020)
Artificial intelligence and data mining techniques have been utilized in numerous spaces to fathom grouping, division, and affiliation, conclusion, and forecast issues. The general point of this uncommon issue is to open a conversation among specialists effectively dealing with calculations and applications. The issue covers a wide assortment of issues for computational intelligence, AI, and time arrangement examinations. The issue of variable determination has been generally examined for various purposes, for example, grouping, characterization or capacity estimate turning into the focal point of many research works where datasets can contain hundreds or thousands factors. Data mining which is now and then additionally called as Knowledge Discovery in Database (KDD) is the way toward breaking down data from alternate points of view and abridging it into valuable information. This Research is process mining can utilize data mining techniques and the examination representation limits so as to make valuable experiences and prescient and ideal models with direct effect on Business models and the open doors that ascent from applying artificial intelligence techniques. This research infers that present day instruments are algorithmically solid however require huge mastery to execute viably.